2018
DOI: 10.1016/j.bjid.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Onabotulinumtoxin type A improves lower urinary tract symptoms and quality of life in patients with human T cell lymphotropic virus type 1 associated overactive bladder

Abstract: Onabotulinum toxin type A intravesically reduced the OABSS with last long effect and improved the quality of life of HTLV-1 infected patients with severe overactive bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…We observed an improvement in subjective symptoms using OABSS, an increase in cystometric capacity. The results of these changes in subjective and objective findings are consistent with other reports by Carneiro et al 17,18 Furthermore, we also examined each item of the OABSS and found that the most important symptom of OAB, urinary urgency, improved after BoNTA therapy in all patients. In addition, we found an elimination of detrusor overactivity through urodynamic studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed an improvement in subjective symptoms using OABSS, an increase in cystometric capacity. The results of these changes in subjective and objective findings are consistent with other reports by Carneiro et al 17,18 Furthermore, we also examined each item of the OABSS and found that the most important symptom of OAB, urinary urgency, improved after BoNTA therapy in all patients. In addition, we found an elimination of detrusor overactivity through urodynamic studies.…”
Section: Discussionsupporting
confidence: 91%
“…Previous reports have indicated that BoNTA intravesical instillation therapy was effective in patients with neurogenic OAB caused by multiple sclerosis or spinal cord injury 15,16 . However, there have been only two reports of the same group on the efficacy of BoNTA in patients with neurogenic OAB due to HAM/TSP refractory to conventional treatment 17,18 . Carneiro et al reported that total OABSS improved from 13.0 to 1.0 in 10 patients (3 probable HAM/TSP and 7 HAM/TSP) 30 days after BoNTA treatment 13 .…”
Section: Discussionmentioning
confidence: 99%